THE ANALYSIS OF LISTENING STRATEGIES USED BY THE ENGLISH DEPARTMENT STUDENTS OF FACULTY OF LANGUAGES AND ARTS OF UNIVERSITAS NEGERI PADANG - Milda Sari Hadi; Aryuliva Adnan; Delvi Wahyuni (Universitas Negeri Padang, 2016)
The purpose of this research were to (1) see the listening strategies used by the students of English department UNP, (2) see the strategies used by the students with higher test score (successful listeners) and the strategies used by the students with lower test score (unsuccessful listeners). The design of this research was descriptive research with population were the second-year students who have taken the Listening 1 subject. The sample of this research was the K4 class with 19 members. The instrument used was the SILL questionnaire which has 50 statements. The result of this research showed that the strategies used by the students from the most to the least were metacogntive strategies, cognitive strategies, compensation strategies, affective strategies, social strategies, and memory strategies. Students with higher test score were shown to use metacognitive strategies with high intensity, followed by cognitive strategies, affective strategies, social strategies, memory strategies and compensation strategies. Students with lower test score were shown to use the metacognitive strategies in medium intensity, followed by affective strategies, compensation strategies, social strategies, cognitive strategies and memory strategies. What differ both students’ category was the intensity of the strategies usage